JBRMR 2017
DOI: 10.24052/jbrmr/v12is01/rcccirtccvfs
|View full text |Cite
|
Sign up to set email alerts
|

RC²@Craftsvilla.Com Craftsvilla is Revolutionizing through Co-creation: Creating Value for Stakeholders

Abstract: Monica and Manoj, founders of Craftsvilla.com, once had an opportunity to interact with rural artisans and designers, in her road trip to Kutch. While interacting, they realized that the middlemen involved in this unorganized retail business were paid very less for the products. The single reason for this disparity they found was the process of taking the art form to retail stores (middleman involved). Most of the artisans, because of no return from the business, want to disengage their future generations to l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 2 publications
0
19
0
Order By: Relevance
“…Different researchers have researched the handicraft sector for its high potential and influence on a country’s economy. Previous studies have identified specific constraints for the Indian handicraft sector, such as lack of marketing support (Banik, 2017; Kumari and Srivasatava, 2016) and distribution concerns (Kumari and Srivasatava, 2016; Pathak et al. , 2017; Tiwari and Dutta, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different researchers have researched the handicraft sector for its high potential and influence on a country’s economy. Previous studies have identified specific constraints for the Indian handicraft sector, such as lack of marketing support (Banik, 2017; Kumari and Srivasatava, 2016) and distribution concerns (Kumari and Srivasatava, 2016; Pathak et al. , 2017; Tiwari and Dutta, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The sector’s potential has generated interest among researchers for conducting further studies. Researchers have identified artisans' unawareness regarding their customers' preferences (Banik, 2017; Kumari and Srivasatava, 2016) and middlemen's interference in the sector's supply chain (Kumari and Srivasatava, 2016; Pathak et al. , 2017; Tiwari and Dutta, 2013) as a few challenges faced by the handicraft sector at the BOP.…”
Section: Introductionmentioning
confidence: 99%
“…According to research, VCC has a moderating effect on the outcomes of experiences ( Meng and Cui, 2020 ). Customers return to retailers who appreciate their ideas, which has resulted in online customer traffic being directed to companies where their ideas are sought, appraised, and included, resulting in VCC ( Pathak et al, 2017 ). However, depending on the type of service, the level of VCC might range from minimal to high.…”
Section: Theory and Hypotheses Developmentmentioning
confidence: 99%
“…The producers of the handicrafts and the potential customers are not in contact with each other leading to a situation where the producers are unaware of the preferences of their customers [1,2]. Another major deterrent is the existence of middlemen in this sector which prevents the craftspeople to earn to their potential, even though the customers are paying handsomely for their creations [2,3,4].…”
Section: Introductionmentioning
confidence: 99%